380 Developing a protocol for pre-operative radiological staging of low-grade endometrial cancer for the thames valley cancer alliance network. (13th November 2020) - Smyth, S; Tasker, G
Abstract : Introduction: Currently the Thames Valley Cancer Network does not undertake any preoperative staging for low-grade endometrial cancer. Consequently a number of patients require completion surgery for bilateral pelvic lymph node dissection. Last year 20/178 cases of low-grade endometrial cancer went on to have completion surgery. This review was designed to consider three proposals for preoperative staging, and to determine the impact on the service delivery – both the caseload for the radiology and surgical teams; and the potential for delaying the treatment times. We aim to reduce the number of cases requiring additional surgery/adjuvant therapy. Methods: We undertook a retrospective review over a six-month period of all cases diagnosed with low-grade endometrial cancer, to determine the final histological staging and how many patients had already had an MRI. Our assumption for the modelling was that the MRI staging would accurately match the final histological staging. We identified 80 cases. 13 patients had already undergone an MRI. We modelled three protocols. Results: No extra cases identified that needed completion surgery and would require reporting standardisation and sonographer up–skilling. Significant pressure on the radiology service. Identified the best detection of cases without excessive demand from the radiology service. Conclusion: All protocols may delay service provision and lead to additional costs. Undertaking an MRI for grade 2 cancers only achieves the greatest benefit with least impact on service, increasing primary surgery but reducing the need for completion surgery/adjuvant therapy. Further investigation of ultrasound scan reporting is on-going.